2020
DOI: 10.5194/essd-2020-183
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Radiosounding HARMonization (RHARM): a new homogenized dataset of radiosounding temperature, humidity and wind profiles with uncertainty

Abstract: Abstract. Observational records are essential for assessing long-term changes in our climate. However, these records are more often than not influenced by residual non‐climatic factors which must be detected and adjusted prior to their usage. Ideally, measurement uncertainties should be properly quantified and validated. In the context of the Copernicus Climate Change Service (C3S), a novel approach, named RHARM (Radiosounding HARMonization), has been developed to provide a harmonized dataset of temperature, h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 31 publications
1
4
0
Order By: Relevance
“…In the most recent decades, a positive trend in RH was also identified by Madonna, Tramutola, et al. (2020) in Europe, in the SH and the tropics. Wind speed shows improvements especially in the NH.…”
Section: Resultssupporting
confidence: 70%
See 1 more Smart Citation
“…In the most recent decades, a positive trend in RH was also identified by Madonna, Tramutola, et al. (2020) in Europe, in the SH and the tropics. Wind speed shows improvements especially in the NH.…”
Section: Resultssupporting
confidence: 70%
“…For both temperature and RH, overall trends in the NH and SH observed at 300 hPa agree with trends at 850 hPa. In the most recent decades, a positive trend in RH was also identified by Madonna, Tramutola, et al (2020) in Europe, in the SH and the tropics. Wind speed shows improvements especially in the NH.…”
Section: Tablementioning
confidence: 82%
“…The quality of atmospheric temperature data is foundational for a wide range of applications in atmospheric sciences, climate research, weather forecasting, ecosystem management, human health, and policy development [145]. It underpins our understanding of climate change, weather patterns, and atmospheric processes, ultimately contributing to informed decisions and actions for a sustainable future [146]. Many studies illustrated that despite RS data quality being of paramount importance, there have been growing challenges such as data discrepancies [147], the lack of homogeneity (in time and space) [148], biases [149], and discontinuities [15] associated with current and historical climate data records obtained using these technologies.…”
Section: Challenges Of Using In Situ Radiosondes and Satellites For U...mentioning
confidence: 99%
“…Significant progress has been made to enhance upper air temperature records acquired utilizing in situ and satellite-based instruments to improve weather forecasting [171], the understanding of atmospheric boundary layer processes [172], and climate change studies [140]. Studies have demonstrated that RSs are still by far the most effective tools for in situ atmospheric temperature observations, but operational meteorological satellites are gradually closing the gap despite their reliance on in situ data for their calibration and validation [77,146,151]. For instance, there have been great advances in RS [141,173] and satellite technology [174].…”
Section: Challenges Of Using In Situ Radiosondes and Satellites For U...mentioning
confidence: 99%
“…At the global scale, more than 1,000 radiosoundings are approximately launched at day and night time each day to characterize the state of the atmosphere (Ladstädter et al ., 2011), although with large sparse coverage in the SH and occasional launches performed on ships to fill the gap over the oceans. The use of radiosounding datasets for climate change studies implies the handling of inhomogeneities caused by frequent changes in instruments, sensor types, observation practices or change in data processing systems (Thorne et al ., 2005; Karl et al ., 2006; Miloshevich et al ., 2006; Simmons et al ., 2014; Madonna et al ., 2020a, 2020b). Radiosondes from different manufacturers are affected by systematic errors, which differ from one type to another (e.g., Dirksen et al ., 2014; Ingleby, 2017).…”
Section: Introductionmentioning
confidence: 99%